Glucose Regulates Glucose Transport and Metabolism via mTOR Signaling Pathway in Bovine Placental Trophoblast Cells - Liyuan Shi; Kun Kang; Zhisheng Wang; Junmei Wang; Jianxin Xiao; Quanhui Peng; Rui Hu; Jia Zhou; Xiaohong Zhang; Ziqi Yue; Huawei Zou; Bai Xue; et al. (Animals, 2023)
It has been confirmed that improving the energy level of the diet contributed to the greater reproductive performance and birth weight of calves in periparturient dairy cows. To investigate the effect of glucose on nutrient transport during fetal development, the bovine placental trophoblast cells (BPTCs) were cultured in media with different glucose concentrations (1, 2, 4, 8, or 16 mg/mL). Subsequently, the BPTCs were cultured in media with 1, 8 mg/mL glucose and 8 mg/mL glucose plus 100 nmol/L rapamycin (the inhibitor of mTOR pathway). Compared with the 1 mg/mL glucose, the addition of 8 mg/mL glucose stimulated cell proliferation, upregulated the mRNA abundance of the glucose transporter GLUT1 and GLUT4, and increased the activity of glucose metabolism-related enzyme glucose-6-phosphate dehydrogenease (G6PD), lactate dehydrogenase (LDHA) and phosphoglycerate kinase 1 (PGK1), as well as adenosine-triphosphate (ATP) content (p < 0.05).Furthermore, compared with the treatment of 1 mg/mL glucose, adding 8 mg/mL of glucose-upregulated gene expression in the mTOR signaling pathway, including phosphatidylinositol3-kinase (PI3K), protein kinase B (Akt), mammalian target of rapamycin (mTOR) and 70 kDa ribosomal protein S6 kinase 2 (P70S6K) (p < 0.05).The supplementation of rapamycin downregulated the gene and protein expression of the mTOR signaling pathway, including mTOR, P70S6K, EIF4E-binding protein 1 (4EBP1), hypoxia-inducible factor 1-alpha (HIF-1α) and gene expression of glucose transporter upregulated by 8 mg/mL glucose (p < 0.05). Thus, these results indicated that the addition of 8 mg/mL glucose regulated the glucose transport and metabolism in BPTCs through the mTOR signaling pathway, thereby promoting the supply of nutrients to fetus.